VD_FINDINFO HC / 2012 / 469 vom 11. Mai 2012 - VD Tribunal cantonal (2012)
EXPERTISE, HONORAIRES | 242 CPC, 94 CPC, 184 al. 3 CPC (CH), 319 let. b ch. 1 CPC (CH), 404 al. 1 CPC (CH), 405 al. 1 CPC (CH)